Total Phallic Reconstruction Using the Radial Artery Based Forearm Free Flap After Traumatic Penile Amputation. Issue 7 (1st July 2016) - Falcone, Marco; Garaffa, Giulio; Raheem, Amr; Christopher, Nim A.; Ralph, David J.
ABSTRACT: Introduction: Although genital injuries in civilian centers are rare, the scenario is completely different in the battlefield. If the penile distal stump is not adequate for primary reimplantation or it cannot be found, then delayed penile reconstruction needs to be considered. Aim: To report a single-center experience with total phallic reconstruction using radial artery based forearm free flap (RAFFF) after penile traumatic loss. Methods: We retrospectively reviewed the clinical records of 10 patients who underwent total phallic reconstruction with the use of the RAFFF from September 2001 through August 2015 after traumatic amputation of the penis. Main Outcome Measures: Patients' baseline features, surgical outcomes, complications, and satisfaction are reported. Results: The average age at the time of penile reconstruction was 36 years (range = 27–52 years). The causes of penile loss were self-amputation owing to an acute schizophrenic episode (n = 2), road traffic accident (n = 3), blast injury (n = 3), donkey bite (n = 1), and Fournier gangrene (n = 1). The average time from the trauma to reconstruction with the RAFFF was 7 years (range = 2–15 years). The urethral stump was adequate for primary anastomosis, with phallic neourethra construction in six patients. The remaining patients had complete avulsion of the penis and were voiding though a perineal urethrostomy. In consequence, they required a two-stage urethroplasty. An acute arterial thrombosis of the microsurgical anastomosis occurred in two patients and was managed successfully with immediate exploration. A neourethra stricture and fistula occurred in one patient, which needed revision. All patients who underwent complete urethral reconstruction could void and ejaculate from the tip of the phallus. After a median follow-up of 51 months (range = 1–114 months), all patients were satisfied with the size, cosmetic appearance, and sensation of the phallus. Six patients underwent inflatable penile prosthesis implantation and could engage in penetrative sex. However, revision surgery was needed in three patients (infection, n = 2; mechanical failure, n = 1). Conclusion: Despite the high incidence of postoperative complications and the possible need for multiple operations, in expert hands and in large-volume centers, penile reconstruction with the RAFFF after traumatic loss of the penis yields excellent results and allows patients to regain sexual and urinary functions.